Exploring anthropometric and laboratory differences in children of varying ethnicities with celiac disease - Rajani, Seema (Pulsus Group Inc, 2014)
BACKGROUND: Celiac disease (CD) is a common autoimmune disorder with an increasing prevalence, including in ethnic minorities. OBJECTIVE: To report the frequency of CD diagnosis in ethnic minorities presenting to a Canadian pediatric celiac clinic and to determine whether ethnic differences exist at diagnosis or follow-up. METHODS: Patients with biopsy-proven CD diagnosed at a multidisciplinary celiac clinic between 2008 and 2011 were identified through the clinic database. Data at referral, and six-month and 12-month follow-ups were collected. These included demographics, self-reported ethnicity, symptoms, anthropometrics and laboratory investigations, including serum immunoglobulin antitissue transglutaminase (aTTG). RESULTS: A total of 272 patients were identified; 80% (n=218) were Caucasian (group 1) and 20% (n=54) were other ethnicities. South Asians (group 2) comprised 81% (n=44) of the minority population. No differences in age or sex were found between the two groups. Group 1 patients presented more often with gastrointestinal symptoms (71% versus 43%; P<0.001), while patients in group 2 presented more often with growth concerns (21% versus 68%; P<0.001). At diagnosis, serum aTTG level was consistently lower in group 1 compared with group 2 (367 IU/mL versus 834 IU/mL; P=0.030). Both groups reported symptom improvement at six months and one year. At the end of one year, aTTG level was more likely to be normal in group 1 compared with group 2 (64% versus 29%; P<0.001). CONCLUSION: Although they represent a minority group, South Asian children comprised a significant proportion of CD patients presenting to a Canadian celiac clinic. South Asian children were more likely to present with growth concerns, which has important implications for timely diagnosis in this population. In addition, the apparent delay in normalization of aTTG levels suggests that careful follow-up and culturally focused education supports should be developed for South Asian children with CD.